Glomerulonefritis focal y segmentaria post COVID-19 en una paciente lúpica - Chávez-Barrios, Vanessa (2024)
We present the case of a 29-year-old woman, with a diagnosis of chronic kidney disease, systemic lupus erythematosus without lupus nephritis criteria, who developed SARS-COV-2 infection, and had acute kidney injury, requiring dialysis. Renal biopsy showed focal segmental glomerulosclerosis, perihilar variant, and evidence of advanced sclerosis. However, renal function recovered several months later, without immunosuppression, so the glomerular damage and acute kidney injury were considered to be secondary to the COVID-19 infection. Since focal and segmental glomerulosclerosis occurred in patients with COVID-19, but its association was infrequent in patients who also had systemic lupus erythematosus, this case is reported.